A new non-entangled quantum secret sharing protocol among different nodes in further quantum networks - Fu, Si-Jia; Zhang, Ke-Jia; Zhang, Long; Hou, Kun-Chi (Frontiers in Physics, 2022)
As an important branch of quantum secure multi-party computation, quantum secret sharing (QSS) can distribute secret information among dishonest network nodes without revealing the secrets. In this paper, a new four-party QSS protocol based on locally indistinguishable orthogonal product (LIOP) states is firstly proposed for quantum network communication. Then the general multiparty QSS model based on LIOP states will be expanded. Combing with the property of LIOP states and obfuscating operation, the source node can send the secrets to different destination nodes in the quantum network. Accordingly, it is proved that the destination nodes have to work together to recover the shared secrets against some existing attacks. Furthermore, no entangled resource and complicated operations are required in the presented protocol. We hope the results could make positive effects to the development of quantum secure communication in future.